Numerical recipes in FORTRAN : the art of scientific computing - Press, William H (Cambridge [England] : Cambridge University Press, 1994)
Counter This is the greatly revised and greatly expanded Second Edition of the hugely popular Numerical Recipes: The Art of Scientific Computing. The product of a unique collaboration among four leading scientists in academic research and industry Numerical Recipes is a complete text and reference book on scientific computing. In a self-contained manner it proceeds from mathematical and theoretical considerations to actual practical computer routines. With over 100 new routines bringing the total to well over 300, plus upgraded versions of the original routines, this new edition remains the most practical, comprehensive handbook of scientific computing available today. Highlights of the new material include: -A new chapter on integral equations and inverse methods -Multigrid and other methods for solving partial differential equations -Improved random number routines - Wavelet transforms -The statistical bootstrap method -A new chapter on "less-numerical" algorithms including compression coding and arbitrary precision arithmetic. The book retains the informal easy-to-read style that made the first edition so popular, while introducing some more advanced topics. It is an ideal textbook for scientists and engineers and an indispensable reference for anyone who works in scientific computing. The Second Edition is availabe in FORTRAN, the traditional language for numerical calculations and in the increasingly popular C language.
Legal matters List of computer programs 1. Preliminaries 2. Solution of linear algebraic equations 3. Interpolation and extrapolation 4. Integration of functions 5. Evaluation of functions 6. Special functions 7. Random numbers 8. Sorting 9. Root finding and nonlinear sets of equations 10. Minimization or maximization of functions 11. Eigensystems 12. Fast Fourier transform 13. Fourier and spectral applications 14. Statistical description of data 15. Modeling of data 16. Integration of ordinary differential equations 17. Two point boundary value problems 18. Integral equations and inverse theory 19. Partial differential equations 20. Less-numerical algorithms References Index of programs and dependencies General index.
Includes bibliographical references (pages 916-919) and index
Keywords: Numerical analysis -- Computer programs; Science -- Mathematics -- Computer programs; FORTRAN (Computer program language)